Formation of the information society and innovative development of the country - Tursunov Sherzod Abdukadirovich; Khidirova Barchinoy Ilkhomovna (Peerian Journals Publishing, 2022)
This article examines the relationship between the formation of the information society and the innovative development of the economy. The article also provides the main features of the information and innovation economy and the key directions of the impact of ICT development on the economic growth of the country
Keywords: information society; information technology; globalization; efficiency